ANALISIS KOMPARATIF LINGKUNGAN KELUARGA, MOTIVASI BERWIRAUSAHA, KOMPETENSI KEWIRAUSAHAAN DAN MINAT BERWIRAUSAHA PADA MAHASISWA ADMINISTRASI BISNIS UNTAG SURABAYA DENGAN MAHASISWA ADMINISTRASI BISNIS UNIVERSITAS HANG TUAH SURABAYA - Ulfa, Tiara Salsabillah; Andayani, Sri; Pujianto, Agung (Research Journal of Social Science and Economics, 2025)
In Indonesia the problem of unemployment is still quite high. The average college graduate is more actively looking for work than creating jobs after graduation. And in fact, after graduating, it does not guarantee that you will immediately get a job. In the city of Surabaya, several private and public universities have provided materials on entrepreneurship, such as UNTAG Surabaya and Hang Tuah University Surabaya. Even though they are both private tertiary institutions, of course the two tertiary institutions have differences in various ways such as the study programs provided, their learning systems and their accreditation. This study aims to determine whether there are differences between variables, namely Family Environment, Entrepreneurial Motivation, Entrepreneurial Competence and Entrepreneurial Interest in Business Administration Students at UNTAG Surabaya and Business Administration Students at Universitas Hang Tuah Surabaya. In this study using quantitative research methods. Using non-probability sampling method with sampling using purposive sampling technique. For data collection techniques from the sample, the researchers distributed questionnaires using the Google form. The data analysis technique used in this study is the homogeneity test and the independent sample t test. Testing the data in this study was assisted by using the SPSS 25 application. Based on the results of the homogeneity test data, it shows that the significance value has a value greater than the significant value, which means that each variable has the same variant. Then based on the results of the t test showed that there was no difference in the Family Environment Variables, Entrepreneurial Motivation, Entrepreneurial Competence, and Entrepreneurial Interest in Business Administration Students at UNTAG Surabaya and Business Administration Students at Hang Tuah University Surabaya. Keywords: Family Environment, Entrepreneurial Motivation, Entrepreneurial Competence, and Interest in Entrepreneurship